Full-Length Transcriptome Sequences Provide Insight Into Hermaphroditism of Freshwater Pearl Mussel Hyriopsis schlegelii - Zeng, Qi; Hu, Beijuan; Blanco, Andres Hortas; Zhang, Wanchang; Zhao, Daxian; Martínez, Paulino; Hong, Yijiang (Frontiers in Genetics, 2022)
The freshwater mussel H. schlegelii is a cultured bivalve in China, and the quality of the pearls produced is affected by the type of gonads. However, because of the lack of a published genome and the complexity of sex determination, research on sex reversal and development of this species is limited. In this study, Illumina RNA-seq and PacBio Isoform Sequencing (Iso-seq) were combined to analyze the gonads of H. schlegelii. A total of 201,481 high-quality transcripts were generated. The study identified 7,922 differentially expressed genes in three group comparisons (females versus males, hermaphrodites versus females, and hermaphrodites versus males). Twenty-four genes were identified as potential sex-related genes, including sox9 and wnt4 involved in sex determination, and vtg, cyp17a1 and 17β-hsd2 involved in gonadal development. We also speculated as to possible pathways for the formation of hermaphroditism in H. schlegelii. The data provide a clear view of the transcriptome for H. schlegelii gonads and will be valuable in elucidating the mechanisms of gonad development.